2014
DOI: 10.1007/s00520-014-2506-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Clostridium difficile infection in adult oncology patients

Abstract: We underscore the urgent need for early recognition and diagnosis of CDI in cancer patients. Our findings indicate a probable association between antibiotic use and CDI incidence, at least in certain cancer, such as breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 31 publications
0
27
1
2
Order By: Relevance
“…A study from the National Institute of Science (NIS) found an almost 5-fold higher incidence of CDI in stem cell transplant recipients and identified GVHD as a specific association with CDI. 14,25 In our study, patients with leukemia, lymphoma, and Kaposi sarcoma had the highest rates of CDI, likely related to prolonged immunosuppression and high rates of chronic antibiotic use. 26 In our study, compared with patients with cancer without CDI, those with CDI were more likely to be older, white, and from the Northeast.…”
Section: Discussionmentioning
confidence: 67%
“…A study from the National Institute of Science (NIS) found an almost 5-fold higher incidence of CDI in stem cell transplant recipients and identified GVHD as a specific association with CDI. 14,25 In our study, patients with leukemia, lymphoma, and Kaposi sarcoma had the highest rates of CDI, likely related to prolonged immunosuppression and high rates of chronic antibiotic use. 26 In our study, compared with patients with cancer without CDI, those with CDI were more likely to be older, white, and from the Northeast.…”
Section: Discussionmentioning
confidence: 67%
“…It has been hypothesized that PPIs alter the colonic flora by facilitating the growth of potentially pathogenic organisms in the gastrointestinal tract . A few studies reported no increased risk of developing CDI if patients are exposed to a PPI . However, significantly more clinical studies found the use of a PPI among hospitalized patients as a risk factor for the development of CDI …”
Section: Discussionmentioning
confidence: 99%
“…27,28 A few studies reported no increased risk of developing CDI if patients are exposed to a PPI. 29,30 However, significantly more clinical studies found the use of a PPI among hospitalized patients as a risk factor for the development of CDI. 14,[31][32][33][34][35] Because our study was not designed to investigate specifically why PPIs may decrease the incidence of CDI among our study patients, the rationale for this finding would require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Oncological patients suffer high rates of CDI due to the frequent presence of risk factors such as recurrent hospitalizations, immunosuppression, antibiotic use (either for prophylactic or therapeutic purposes), chemotherapy and the use of enteral and parenteral nutrition [ 24 ]. Despite the suggestion that patients with gastrointestinal tumors have a lesser predisposition to CDI and that patients with breast cancer are more prone to this infection, up to now, no clear relationship between the type of cancer and the risk of CDI has been described [ 25 ]. Similarly, some chemotherapy drugs, such as platinum-based agents, taxanes and DNA-topoisomerase inhibitors, have been reported to be more related to CDI than others [ 26 ].…”
Section: Infection In Oncological Patientsmentioning
confidence: 99%
“…Similarly, some chemotherapy drugs, such as platinum-based agents, taxanes and DNA-topoisomerase inhibitors, have been reported to be more related to CDI than others [ 26 ]. However, other studies did not find that any specific chemotherapy drug was especially related to a higher risk of CDI [ 25 ]. The pathogenesis of chemotherapy-related CDI is not well understood.…”
Section: Infection In Oncological Patientsmentioning
confidence: 99%